Research on planning and design of land consolidation based on extension engineering method - XUE Ji-bin; WU Ci-fang; YE Yan-mei; XU Bao-gen (浙江大学学报. 农业与生命科学版)
Extension engineering is a new subject that takes the exploiting & innovating rules and means as research object. According to the characteristics of land consolidation industry in China, using matter-element theory, the extensibility of land resources is analyzed, and then the framework of matter-element models for land consolidation is formed. Finally, taking the land consolidation planning and design as an example at Mazhu Town site of Yuyao County, Zhejiang Province, China, the paper researched on how to form the scheme that are in accord with the programming targets by matter-element transformation. The result is believed to provide new means and ideas for the planning and design.